X-point and divertor filament dynamics from gas puff imaging on TCV. (1st October 2022) - Wüthrich, C.; Theiler, C.; Offeddu, N.; Galassi, D.; Oliveira, D.S.; Duval, B.P.; Février, O.; Golfinopoulos, T.; Han, W.; Marmar, E.; Terry, J.L.; Tsui, C.K.; et al.
Abstract: A new gas puff imaging diagnostic has been installed on the TCV tokamak, providing two-dimensional insights into scrape-off-layer (SOL) turbulence dynamics above, at and below the magnetic X-point. A detailed study in L-mode, attached, lower single-null discharges shows that statistical properties have little poloidal variations, while vast differences are present in the 2D behaviour of intermittent filaments. Strongly elongated filaments, just above the X-point and in the divertor far-SOL, show a good consistency in shape and dynamics with field-line tracing from filaments at the outboard midplane, highlighting their connection. In the near-SOL of the outer divertor leg, short-lived, high frequency and more circular (diameter ∼15 sound Larmor radii) filaments are observed. These divertor-localised filaments appear born radially at the position of maximum density and display a radially outward motion with velocity ≈400 m s −1 that is comparable to radial velocities of upstream-connected filaments. Conversely, in these discharges ( B → × ∇ B pointing away from the divertor), these divertor filaments' poloidal velocities differ strongly from those of upstream-connected filaments. The importance of divertor-localised filaments upon radial transport and profile broadening is explored using filament statistics and in situ kinetic profile measurements along the divertor leg. This suggests that these filaments contribute significantly to electron density profile broadening in the divertor.